พฤติกรรมการรับน้ำหนักตามแนวแกนของเสาเหล็กภายใต้สภาวะอุณหภูมิสูง - อดิเทพ แสนทวีสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research is aimed to investigate the behavior of axially loaded steel columns under high temperature conditions in order to obtain preliminary data for the steel column design without fire protection. For the current study the limiting temperature is obtained, based upon EN 1993-1-2 standard, through testing steel column specimens of H 100x100x6x8 mm section and 1.4 m in length axially loaded under increasing temperatures in accordance with the BS 476 standard time–temperature relationship. The limiting temperatures are subsequently used to determine the time–temperature conditions in examining the behavior of axially loaded steel column under natural fire condition. The nature fire condition is simulated using the Barnett fire design (BFD) curve with varying maximum temperatures in terms of percentages of the limiting temperature values. The test results are compared with the results obtained from the analytical model of axially loaded steel columns under increasing temperature by using the finite element method. It has been found from the comparison that the support reactions, the limiting temperatures and the deflection of the steel columns obtained from the analytical models are close to the test results. The behavior of axially loaded steel columns is further investigated with varying load ratios and high temperature conditions through supplementary analytical models, covering five load ratios, i.e. 0.15, 0.20, 0.30, 0.40 and 0.50, with increasing temperatures according to BS 476 standard (for determining the limiting temperatures) and the BFD curve using seven values of the maximum fire temperature/limiting temperature ratio of 0.50, 0.60, 0.70, 0.80, 0.90, 0.95 and 1.00, respectively. It has been found from the analyses that the steel columns subjected to higher load ratios show lower limiting temperatures and shorter time to failure, while the support reactions increase during the heated period. In addition, under a specified maximum temperature, the steel columns under the increasing temperature in accordance with the BFD curve show higher values of support reactions compared with the BS 476 standard due to the longer period of fire growth and thus a higher level of steel expansion. It has also been observed that the axial load capacity of the steel columns under a constant temperature of 500 °C obtained from the analytical models is similar to that computed based on EN 1993-1-2 when the slenderness ratio is higher than 50. Moreover, the axial load capacity of the steel columns obtained from the models is comparable to the test results of Kuo – Chen et al. (2005) when the slenderness ratio is higher than 52. For a trial design, a steel column of H100x100x6x8 mm section and 1.4 m in length subjected to 7-ton axial load is designated to have a 60-minute fire resistance rating under the increasing temperature condition according to the BFD curve with the maximum temperature at 60% of the limiting temperature. It has been found from testing the steel column under the specified condition that the column fails at 56 minutes.